Self-perceptions of aging: a conceptual and empirical overview - Diehl, Manfred; Wahl, Hans-Werner (Current opinion in psychology, 2024)
This article defines self-perceptions of aging (SPA) as individuals' perceptions, expectations, and experiences regarding their own process of growing old(er). As such, SPA are considered a critically important element of the aging self. Furthermore, the authors present a heuristic model that positions adults' SPA within a lifespan developmental and cultural-societal context and elaborates distal and proximal antecedents, process modes, and developmental outcomes. The remainder of the article summarizes recent empirical findings and discusses future challenges and directions.
Available online 15 November 2023, version of record 7 December 2023
Gesehen am 27.03.2024